2016
DOI: 10.1073/pnas.1605031113
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of an Fe-S cluster-containing fumarate hydratase enzyme from Leishmania major reveals a unique protein fold

Abstract: Fumarate hydratases (FHs) are essential metabolic enzymes grouped into two classes. Here, we present the crystal structure of a class I FH, the cytosolic FH from Leishmania major, which reveals a previously undiscovered protein fold that coordinates a catalytically essential [4Fe-4S] cluster. Our 2.05 Å resolution data further reveal a dimeric architecture for this FH that resembles a heart, with each lobe comprised of two domains that are arranged around the active site. Besides the active site, where the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(75 citation statements)
references
References 35 publications
(20 reference statements)
6
62
0
Order By: Relevance
“…A recent study has reported the inhibition of TcFH by DL-MSA with a K i value of 4.2 ± 0.5 µM while no effect was observed on the class II human FH (22). The reason for DL-MSA's high specificity for class I FH must stem from the presence of 4Fe-4S cluster that interacts with the C2-hydroxyl group of malate (11). Replacement of the hydroxyl group with a thiol probably leads to tight binding through Fe-S interaction.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A recent study has reported the inhibition of TcFH by DL-MSA with a K i value of 4.2 ± 0.5 µM while no effect was observed on the class II human FH (22). The reason for DL-MSA's high specificity for class I FH must stem from the presence of 4Fe-4S cluster that interacts with the C2-hydroxyl group of malate (11). Replacement of the hydroxyl group with a thiol probably leads to tight binding through Fe-S interaction.…”
Section: Discussionmentioning
confidence: 98%
“…Class I fumarases display substrate promiscuity; apart from catalyzing the interconversion of fumarate and malate, these enzymes also interconvert S, S-tartrate and oxaloacetate and, mesaconate and S-citramalate with varying catalytic efficiencies (9,10). The 4Fe-4S cluster is bound to the enzyme by 3 metalthiolate bonds formed between 3 conserved cysteine residues in the protein and 3 ferrous ions (11). The fourth iron in the cluster, proposed to be held loosely by a hydroxyl ion is thought to be directly involved in substrate binding and catalysis as seen in the enzyme aconitase (12,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has reported the inhibition of TcFH by DL-MSA with a K i of 4.2 ± 0.5 µM while no effect was observed on the class II human FH (22). Interestingly, DL-MSA is not a substrate for PfFH as seen by spectrophotometric assays at 240 nm with 10 mM DL-MSA and 1 µM enzyme that failed to show either formation of the enediolate intermediate or the product fumarate through the liberation of H 2 S. The reason for DL-MSA's high specificity for class I FH must stem from the presence of 4Fe-4S cluster that interacts with the C2-hydroxyl group of malate (11). Replacement of the hydroxyl group with a thiol probably leads to tight binding through Fe-S interaction.…”
Section: Pffh Complements Fumarase Deficiency In E Coli-mentioning
confidence: 98%
“…Class I fumarases display substrate promiscuity; apart from catalyzing the interconversion of fumarate and malate, these enzymes also interconvert S,S-tartrate and oxaloacetate and, mesaconate and S-citramalate with varying catalytic efficiencies (9,10). The 4Fe-4S cluster is bound to the enzyme by 3 metal-thiolate bonds formed between 3 conserved cysteine residues in the protein and 3 ferrous ions (11). The fourth iron in the cluster proposed to be held loosely by a hydroxyl ion, is thought to be directly involved in substrate binding and catalysis as seen in the enzyme aconitase (12,13).…”
Section: Introductionmentioning
confidence: 99%